2011
DOI: 10.4161/auto.7.3.14583
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of cells dying through autophagy induces inflammasome activation and IL-1β release in human macrophages

Abstract: Phagocytosis of naturally dying cells usually blocks inflammatory reactions in host cells. We have recently observed that clearance of cells dying through autophagy leads to a pro-inflammatory response in human macrophages. Investigating this response further, we found that during engulfment of MCF-7 or 293T cells undergoing autophagic death, but not apoptotic or anoikic ones, caspase-1 was activated and IL-1β was processed, then secreted in a MyD88-independent manner. Autophagic dying cells were capable of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 32 publications
(48 reference statements)
3
41
1
1
Order By: Relevance
“…68 Radiotherapy triggers ATP release from dying tumor cells through its interaction with the P2 Â 7 purinergic receptor, 69 possibly resulting in the activation of the NLRP3-ASC-inflammasome axis and subsequent secretion of IL-1b. 70 We and others recently showed that oncolytic viruses induce secretion of extracellular ATP from human cancer cells (Figure 1). 9,65 Unlike ecto-CRT induction, the release of ATP and HMGB1 is triggered by a range of death-inducing stimuli, and is not restricted to induction in apoptotic cell death.…”
Section: Adenosine Triphosphatementioning
confidence: 95%
“…68 Radiotherapy triggers ATP release from dying tumor cells through its interaction with the P2 Â 7 purinergic receptor, 69 possibly resulting in the activation of the NLRP3-ASC-inflammasome axis and subsequent secretion of IL-1b. 70 We and others recently showed that oncolytic viruses induce secretion of extracellular ATP from human cancer cells (Figure 1). 9,65 Unlike ecto-CRT induction, the release of ATP and HMGB1 is triggered by a range of death-inducing stimuli, and is not restricted to induction in apoptotic cell death.…”
Section: Adenosine Triphosphatementioning
confidence: 95%
“…12,23 DC inflammasome activation results in the synthesis and secretion of IL-1β, where secreted IL-1β initiates further proinflammatory events. 12,23,26 In addition to the classic components of ICD, other molecules upregulated in response to radiotherapy have been shown to be involved in antitumor immunity. For example, major histocompatibility complex Class I molecules present endogenous peptides to cytotoxic T lymphocytes and allows for the recognition of tumor cells by cytotoxic T lymphocytes, resulting in efficient tumor cell kill.…”
Section: Immunogenic Cell Deathmentioning
confidence: 99%
“…[36][37][38] In another context, autophagic dying cells have been found to undergo (phosphatidylserine (PtdSer)-based) 8 phagocytosis associated with inflammatory response. 39 Thus in the future it would be crucial to identify the molecular determinants driving the recognition and phagocytic removal of cancer cells dying through these non-apoptotic pathways.…”
Section: Regulated Necrosismentioning
confidence: 99%